Caracterización fenotípica y producción en plantas R2 de arroz (Oryza sativa L., ssp. japonico) obtenidas mediante cultivo in vitro de anteras - García Bustamante, Emilio Fabián (2017)
VIII. SUMMARY The present study consisted of the phenotypic characterization and production in rice R2 plants (Oryza sativa L., ssp japonica) obtained by in vitro anther culture. The cultivation of anther is a complementary tool in genetic improvement; has the advantage of fixing the desired characteristics in a shorter time than required, compared to the traditional pedigree method. This research was planned with the purpose of determining the phenotypic and production characteristics in R2 plants of japonica rice, derived from anther culture. The trial was established in the greenhouse of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km 7 ½, via Babahoyo - Montalvo, Babahoyo county, province of Los Ríos. The evaluated variables were based on the CIAT Varietal Rice Descriptor (1993), considering the quantitative and qualitative variables in the seedling stages, at the time of flowering and in the state of maturation. In the evaulated variables, an analysis of variance was applied to detect statistical significance among the treatments and the Tukey test was applied to 5%. Most of the analyzed variables reported statistical significance, which allowed determining the most important variables and detecting the best agronomic and production behavior among the individuals of the crosses evaluated, which influenced the moment of their selection. The individuals of JP003 / Puyón (P15) and JP004 / Puyón (P14b) turned out to be of better behavior; of good vegetative vigor, predominant growth habit, tillering capacity, plant height, panicle exercice, grains per panicles, panicle length and yield per plant. It is concluded that by applying a minutious phenotypic characterization study to the R2 materials obtained by in vitro anther culture, genotypes with good agronomic and production behavior were identified, where the individuals of the JP003 / Puyón (P15) cross presented 32 favorable characteristics and the JP004 / Puyón (P14b) presented 33 characteristics, from a total of 58 evaluated variables in the study. It is recommended to continue with the evaluations of production, resistance to pests and diseases of the selected materials R3 in field conditions, since they are genetic materials of great importance, which could be converted into new japonica varieties for the national market.